2007
DOI: 10.1007/s10903-007-9063-9
|View full text |Cite
|
Sign up to set email alerts
|

Research with Severely Mentally Ill Latinas: Successful Recruitment and Retention Strategies

Abstract: Individuals from minority groups in the United States have been found less likely than non-Hispanic whites to participate in research studies. The recruitment and retention of individuals from minority groups has also proved challenging. We describe the challenges that we encountered in recruiting and retaining a sample of severely mentally ill Mexican and Puerto Rican ethnicity for a study of the context of HIV risk. We recruited women in San Diego County, California and northeastern Ohio who were between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 33 publications
0
90
0
Order By: Relevance
“…The publication outlined five recommended elements of outreach: understanding the study population, establishing an explicit outreach plan, achieving agreement on research plans, designing and conducting evaluations, and establishing and maintaining communication. The first element of outreach seems particularly crucial to examine when working with Latino families, given that the population is so culturally diverse (National Institutes of Health (NIH 2002;US Census Bureau 2003a) and faces a number of practical and cultural barriers that likely prevent participation in clinical child research (Gilliss et al 2001;Le et al 2008;Loue and Sajatovic 2008;Preloran et al 2001;Rodriguez and Rodriguez 2006;Yancey et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The publication outlined five recommended elements of outreach: understanding the study population, establishing an explicit outreach plan, achieving agreement on research plans, designing and conducting evaluations, and establishing and maintaining communication. The first element of outreach seems particularly crucial to examine when working with Latino families, given that the population is so culturally diverse (National Institutes of Health (NIH 2002;US Census Bureau 2003a) and faces a number of practical and cultural barriers that likely prevent participation in clinical child research (Gilliss et al 2001;Le et al 2008;Loue and Sajatovic 2008;Preloran et al 2001;Rodriguez and Rodriguez 2006;Yancey et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The little available research in this area, which will be discussed below, has largely been exploratory and qualitative in nature and has resulted in general recommendations related to combating practical and cultural barriers to Latino participation in clinical research (e.g., Gilliss et al 2001;Le et al 2008;Loue and Sajatovic 2008;Preloran et al 2001;Rodriguez and Rodriguez 2006;Yancey et al 2006), but has not provided empirical evidence supporting the effectiveness of the recommended modifications (Yancey et al 2006). Researchers must now begin to quantitatively examine these modifications, as well as individual and cultural factors that may shed light on which modifications are most effective for whom.…”
Section: Introductionmentioning
confidence: 99%
“…Andersen and Newman's [16] framework helps illuminate new and important Predisposing "Psychological Coping" Belief barriers specific to this co-morbid population, that are not specifically indicated in the literature (i.e., "feeling better;" "not interested;" "emotional stress;" grief over "loss;" untreated panic attacks; and anxiety over fertility issues). However, there are also other possible relevant cultural barriers (i.e., distrust, fear, and language issues [26,31,32]) and provider barriers (i.e., inflexibility on the researchers' part to reschedule, lack of feedback from the research team [26]) indicated in the literature which were not captured in this study's medical record documentation. Such cultural and provider barriers are more sensitive issues that are less commonly explored and documented.…”
Section: Discussionmentioning
confidence: 93%
“…This study identifies many of the same barriers found in the literature that categorize Latino clinical trial retention barriers: familial relationships and issues [22], lack of transportation, employment interferences [23], economic stress [24] and financial costs [25], insufficient caregiving resources to meet demands [26], practical barriers [24,27], like interference with other top priorities of life such as work and family obligations [26], and systems barriers [28][29][30]. Andersen and Newman's [16] framework helps illuminate new and important Predisposing "Psychological Coping" Belief barriers specific to this co-morbid population, that are not specifically indicated in the literature (i.e., "feeling better;" "not interested;" "emotional stress;" grief over "loss;" untreated panic attacks; and anxiety over fertility issues).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation